Co-pelletization of Industrial Sewage Sludge and Rice Straw: Characteristics and Economic Analysis - Duangjaiboon, Krittidej; Kitiwan, Mettaya; Kaewpengkrow, Prangthip Rittichote (International Journal of Renewable Energy Development, 2021)
The disposal of industrial sewage sludge is one of the most serious environmental problems in Thailand. Moreover, the disposal expense is considered as the production cost to the manufacturer. Therefore, the concept of waste-to-energy technology (WTE) is applied to solve this problem. This study aimed to study the effect of sewage sludge and rice straw proportions on the properties of co-pellets. Here, the production of co-pelleted sewage sludge from the canned food industry, combined with biomass (rice straw), was performed using a lab-scale pelletization machine. The pellets consisted of sewage sludge (SS) and rice straw (RS) with sewage sludge ratios of RS100:SS0, RS50:SS50, RS35:SS65, RS25:SS75, and RS0:SS100. The co-pellets produced were characterized for physicochemical properties and calorific heating values. In addition, the benefit to cost ratio (B/C), internal rate of return (IRR), and payback period (PB) from the utilization of co-pellets were studied. The results suggest that the proportion of sewage sludge affects the properties of the co-pellets. The optimum sewage sludge to rice straw ratio at RS0:SS100Â is considered to have good fuel combustion properties. It is suitable for the production of co-pellets because of its high volatility and low ash slagging content